Budget Deficits and Fiscal Decentralization: Evidence from Central and Eastern Europe - Makreshanska mladenovska, Suzana; Petrevski, Goran (Macedonian Academy of Sciences and Arts, 2019)
This paper provides empirical evidence on the association between decentralization and fiscal performance of the general government on a panel of 11 former transition countries during 1991-2016, controlling for the effects of various demographic, institutional, and macroeconomic variables. The main findings from the empirical investigation suggest that decentralizing government is associated with better fiscal performance activities in Central and Eastern Europe (CEE) countries. However, we show that only the extent of fiscal decentralization matters for fiscal discipline notwithstanding the composition of local revenue Also, we find that fiscal rule may have favourable effects on the fiscal discipline, though their magnitude is rather modest.
Keywords: iscal decentralization, Budget deficits, Central and Eastern Europe, Panel data models